Review of the genus Ageleradix Xu & Li, 2007 (Araneae, Agelenidae), with descriptions of three new species - Yan-Nan Mu; Lu-Yu Wang; Tian-Yu Ren; Yuan Tian; Zhi-Sheng Zhang (ZooKeys)
The spider genus Ageleradix Xu & Li, 2007 is reviewed. Three new species are described: A. dulong Mu, Wang & Zhang, sp. nov. (♂♀, Yunnan), A. jinfoshan Mu, Wang & Zhang, sp. nov. (♀, Chongqing) and A. nangunhe Mu, Wang & Zhang, sp. nov. (♂♀, Yunnan). A key to all nine species of Ageleradix is provided, and the genus is split into three species-groups.